Terahertz reconfigurable dielectric metasurface hybridized with vanadium dioxide for two-dimensional multichannel multiplexing - Wang, Ling; Yang, Yang; Gao, Feng; Teng, Shuhua; Tan, Zhi-Guo; Zhang, Xing; Lou, Jun; Deng, Li (Frontiers in Physics, 2022)
The metasurface hybridized with vanadium dioxide (VO2) can be dynamically tuned, which has attracted enormous attention in recent years and orbital angular momentum (OAM) multiplexing based on metasurfaces has shown promising prospects in terahertz communications. However, existing research on VO2 metasurface focuses on the metallic metasurface. The dielectric VO2 metasurface used for OAM multiplexing is rarely reported to the present. This paper proposed a terahertz reconfigurable dielectric metasurface hybridized with VO2 for two-dimensional multichannel multiplexing combing with spatial and frequency domains. The metasurface works in both reflection and transmission modes and simultaneously the polarization control and operating frequency band regulation can be realized by switching the VO2 from the metallic state to the insulator state. For the reflective or transmissive metasurface, when 4×M-channel (M is a positive integer) off-axis plane waves are incident on the metasurface, the co-polarization reflected or cross-polarization transmitted waves are transformed into 4×M-channel orthogonal on-axis beams with topological or frequency orthogonality. A metasurface composed of 14×14 unit cells is designed for verification. The simulated result shows that two-dimensional 12-channel multiplexing combing with OAM and frequency by the designed metasurface can be realized on the reflection and transmission modes in two different frequency bands. The proposed metasurface has great potential in terahertz communications.